Bolt Load Changes During Initial Face Advance And Cross-Cut Breakthrough - Steve Signer (International Conference on Ground Control in Mining, 2004)
The San Juan Mine and the National Institute for Occupational Safety and Health conducted a study to measure how development mining effected bolt loads. Twelve fully grouted, instrumented roof bolts were installed at two three-way intersections as part of the standard bolting pattern. Newly developed miniature data acquisition systems (MIDAS) were used to measure bolt load changes during initial face advance and cross-cut breakthrough. The effects of cut placement and depth on roof bolt loads were studied This test showed how bolt loads increased at five positions along the bolt length during initial mining. Both entry advance and cross-cut breakthrough produced a similar percentage of increase in bolt loads. Geologic differences between the test sites were probably responsible for the differences in amounts of bolt loading. The test site with more top coal and a higher rock quality designation (RQD) had lower bolt loads.